Violência e desigualdade social sob o olhar da Teoria Crítica - Maria Aparecida Pinto de Souza (2021)
The present study is an effort to unveil, through a critical analysis, the origins of violence and social inequality from the perspective of critical theory thinkers today. This dissertation is an attempt to give visibility to something naturalized and invisible: the structural violence arising from the relationship of capitalist domination against the class that lives off work, which systematically generates structural poverty. We believe that the investigation of the phenomenon – violence and social inequality – Will be of fundamental importance for us to understand the factors that are causing the increase in violence in our society. The interest in opting for this theme was not random, as we observe, in the current scenario, a considerable increase in the occurrence of violence and social inequality. Faced with the expansion of contemporary capitalism and the productive restructuring of work, a serious unemployment crisis was generated within the production system. Other relevant aspects of this issue in the current Brazilian situation are allied to the globalization process, and the technological changes of the digital age Demystifying the world of work is the purpose we propose to understand the phenomenon of violence, which is increasingly growing in Brazilian society. The methodology used was a theoretical review of the main concepts of scholars about capitalism, alienated labor and structural unemployment.